Preparation of long-acting microspheres loaded with octreotide for the treatment of portal hypertensive. (1st January 2021) - Han, Bing; Tang, Huan; Liang, Qiming; Zhu, Ming; Xie, Yizhuo; Chen, Jinglin; Li, Qianwen; Jia, Juan; Li, Yan; Ren, Zhihui; Cong, Dengli; Yu, Xiaofeng; et al.
Abstract: The purpose of this study was to optimize the preparation method of injectable Octreotide microspheres. To explore the correlation between the solvent system and the general properties of microspheres to reduce burst release and enable them to be used for portal hypertension. Octreotide microspheres were prepared by modified double emulsion solution evaporation method after optimizing preparation conditions. The results showed that Octreotide microspheres had a particle size of 57.48 ± 15.24 μm, and the initial release was significantly reduced. In vitro release and in vivo pharmacokinetic data indicated that Octreotide was released stably within 1200 h. The effects on portal vein pressure, liver tissue morphology and other related indexes were observed after administration. As obvious results, injection of Octreotide microspheres could significantly reduce portal vein pressure and reduce the portal vein lumen area in experimental cirrhotic portal hypertensive rats. The optimized Octreotide PLGA microsphere preparation has been proved to have a good effect on PHT in vivo after detecting aminotransferase (AST) and alanine aminotransferase (ALT) activity, liver tissue hydroxyproline (Hyp) content, serum and liver tissue malondialdehyde (MDA) levels, plasma prostacyclin (PGI2 ) levels, and liver tissue tumor necrosis factor (TNFα) content. In addition, serum and liver tissue superoxide dismutase (SOD) activity and liver tissue glutathione (GSH) content, plasma thromboxane (TXA2 ), serum nitric oxide (NO), liver tissue nitric oxide synthase (NOS), and plasma and liver tissue endothelin (ET) were significantly increased.